Giant morphea-form basal cell carcinoma of the umbilicus: Successful debulking with vismodegib. (2nd May 2018) - Orduz Robledo, Mariana; Lebas, Eve; Reginster, Marie-Annick; Baghaie, Mahmoud; Groves, Sabine; Nikkels, Arjen F
Basal cell carcinoma of the umbilicus is very rare. The nodular subtype is the main representative. Giant basal cell carcinomas represent around 1% of all basal cell carcinomas. The hedgehog pathway inhibitor vismodegib is indicated for advanced basal cell carcinoma and CD56-negative immunostaining seems indicative for successful treatment. A 54-year-old man presented a 10 cm × 14 cm large and 4.5 cm deep morphea-form basal cell carcinoma with faint immunohistochemical CD56 expression arising from the umbilicus. A sequential treatment was initiated with debulking using vismodegib 150 mg per day for 4 months, followed by reconstructive surgery. To the best of our knowledge, this is the first report of a giant basal cell carcinoma of the morphea-form type of the umbilicus. The sequential treatment plan reduces the duration of vismodegib inherent adverse effects and significantly reduces the tumor mass prior to surgery. Besides increasing adherence to vismodegib treatment, this approach facilitates the surgical technique and improves cosmetic outcome.